Structural Analysis Reveals the Substrate‐Binding Mechanism for the Expanded Substrate Specificity of Mutant meso‐Diaminopimelate Dehydrogenase. Issue 6 (6th March 2015) - Liu, Weidong; Guo, Rey‐Ting; Chen, Xi; Li, Zhe; Gao, Xiuzhen; Huang, Chun‐Hsiang; Wu, Qiaqing; Feng, Jinhui; Zhu, Dunming
Abstract A meso‐diaminopimelate dehydrogenase (DAPDH) from Clostridium tetani E88 (CtDAPDH) was found to have low activity toward the D‐amino acids other than its native substrate. Site‐directed mutagenesis similar to that carried out on the residues mutated by Vedha‐Peters et al. resulted in a mutant enzyme with highly improved catalytic ability for the synthesis of D‐amino acids. The crystal structures of the CtDAPDH mutant in apo form and in complex with meso‐diaminopimelate (meso‐DAP), D‐leucine (D‐leu), and 4‐methyl‐2‐oxopentanoic acid (MOPA) were solved. meso‐DAP was found in an area outside the catalytic cavity; this suggested a possible two‐step substrate‐binding mechanism for meso‐DAP. D‐leu and MOPA each bound both to Leu154 and to Gly155 in the open form of CtDAPDH, and structural analysis revealed the molecular basis for the expanded substrate specificity of the mutant meso‐diaminopimelate dehydrogenases.